Theoretical Simulation and Parametric Optimization of Parabolic Through Solar Steam Generation System Under Tropical Climate - Masood, Rizwan (2017)
According to the Eleventh Malaysia Plan (2015), Malaysia Government has set a voluntary target to reduce Greenhouse Gasses emission intensity of GDP by up to 40% compared to 2005 levels by the year 2020.